2022
DOI: 10.1002/bio.4313
|View full text |Cite
|
Sign up to set email alerts
|

An efficient differential sensing strategy for phenolic pollutants based on a nanozyme with polyphenol oxidase activity

Abstract: To realize the efficient differential sensing of phenolic pollutants in sewage, a novel sensing strategy was successfully developed based on a nanozyme (GMP‐Cu) with polyphenol oxidase activity. Phenolic pollutants can be oxidized using GMP‐Cu, and the oxidation products reacts subsequently with 4‐aminoantipyrine to produce a quinone‐imine compound. The absorption spectra of final quinone‐imine products that resulted from different phenolic pollutants showed obvious differences, which were due to the interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Such laccase mimic-based assays have also been developed for phenol sensing. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][124][125][126][127][128] In a representative study, Liu's group synthesized a guanosine monophosphate (GMP) chelated Cu-based material and found that the material exhibited excellent laccase-mimicking activity. 121 They employed epinephrine as a laccase substrate and found that a colored oxidation product was formed (Fig.…”
Section: Detection Of Phenolic Pollutantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such laccase mimic-based assays have also been developed for phenol sensing. [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][124][125][126][127][128] In a representative study, Liu's group synthesized a guanosine monophosphate (GMP) chelated Cu-based material and found that the material exhibited excellent laccase-mimicking activity. 121 They employed epinephrine as a laccase substrate and found that a colored oxidation product was formed (Fig.…”
Section: Detection Of Phenolic Pollutantsmentioning
confidence: 99%
“…Fortunately, there are several nanozyme-based sensors arrays developed to realize this goal. 106,120,123,[126][127][128][129][130][131] For example, we proposed a high-performance and convenient sensor array for optical discrimination of phenolic contaminants through using Fe 3 O 4 NPs as a peroxidase imitator. 106 The synthesized Fe 3 O 4 NPs exhibited high activity to catalytically accelerate the reaction of 4-AAP, H 2 O 2 and phenolic substances, presenting a notable Environmental Science: Nano Critical review color change to reveal the content of the analyte (Fig.…”
Section: Detection Of Phenolic Pollutantsmentioning
confidence: 99%